Oat Plant Amyloids for Sustainable Functional Materials (Adv. Sci. 4/2022). Issue 4 (3rd February 2022) - Zhou, Jiangtao; Li, Ting; Peydayesh, Mohammad; Usuelli, Mattia; Lutz‐Bueno, Viviane; Teng, Jie; Wang, Li; Mezzenga, Raffaele
Abstract : Functional Amyloid Materials An oat‐globulin amyloid aerogel sits on the awns of oat spikelet. This aerogel was fabricated by plant‐based oat‐globulin amyloid fibrils, made from oat seeds, as those shown in the photo. As a sustainable material source with diverse functionalities, the ensued amyloids were demonstrated as ideal scaffold for material templates such as aerogels, hydrogels, water purification membranes and bioelectrodes. More details can be found in article number 2104445 by Raffaele Mezzenga and co‐workers.